Community hospitals of the future—challenges and opportunities - Phang, Sean Kia Ann; Lin, Ming; Kho, Yong Xiang; Toh, Rui Jie Rachel; Kuah, Ting Ting; Lai, Yi Feng; Xie, JiaJing Kim (Frontiers in Health Services, 2023)
Background Medical training through specialization and even subspecialization has contributed significantly to clinical excellence in treating single acute conditions. However, the needs of complex patients go beyond single diseases, and there is a need to identify a group of generalists who are able to deliver cost-effective, holistic care to patients with multiple comorbidities and multi-faceted needs. Community hospitals (CHs) are a critical part of Singapore's shift toward a community-centric care model as the population ages. Community Hospitals of the Future (“CHoF”) represent a series of emerging conversations around approaches to reimagine and redesign care delivery in a CH setting in response to changing care needs. Methods An environmental scan in the CH landscape using semi-structured interviews was conducted with 26 senior management, management, and working-level staff from seven community hospitals in Singapore. This environmental scan aims to understand the current barriers and future opportunities for CHs; to guide how CHs would have to shift in terms of (i) care delivery and resourcing, (ii) information flow, and (iii) financing; and to conceptualize CHoF to meet the changing care needs in Singapore. Findings The analysis of all transcripts revealed four broad sections of themes: (i) current care delivery in CHs, (ii) current challenges of CHs, (iii) future opportunities, and (iv) challenges in reimagining CHs. An emerging theme regarding the current key performance indicators used also surfaced. Resource limitations and financing structure of CH surfaced as limitations to expanding its capability. However, room for expansion of CH roles tapping on the current expertise were acknowledged and shared. Conclusion With the current issues of (i) rapidly aging population, (ii) specialist-centric healthcare system, and (iii) fragmentation of care ecosystem, there is a need to further understand how CHoF can be modeled to better tackle them. Therefore, several important questions have been devised to land us in a microscopic view on how to develop CHoF in the right constructs. Demographic changes, patient segmentation, service and regulatory parameters, patient's perspective, care delivery, and financial levers (or lack of) are some of the categories that the interview questions looked into. Therefore, the data gathered would be used to guide and refine the concept of CHoF.